Constitutional and legal aspects of the execution of the constituent entities’ powers in the field of legislation on administrative offences - O. Kozhevnikov (Правоприменение, 2018)
The subject of the paper is constituent entities’ powers in federative state concerning the establishment of the administrative responsibility for breach regional and municipal rules.The purpose of the paper is to justify the need for new approaches to the delimitation of the constituent entities’ jurisdiction in the field of legislation on administrative offences, up to the allocation of administrative-tort legislation in the exclusive jurisdiction of the Federation.The methodology. General and special scientific methods of cognition were applied: systemic, comparative legal, formal logical. The analysis of legislative and law-enforcement practice of the constituent entities of the Russian Federation, the legal decisions of the Con-stitutional Court of the Russian Federation, is also used.The main results and scope of their application. The constituent entities of the Russian Federation, making legal acts in the field of legislation on administrative offenses, are not always properly take into account the boundaries of their competence in the field of establishment of administrative responsibility for committing administrative offences for breach regional and municipal rules. The compliance of such constituent entities’ authority to es-tablish this type of responsibility with the provisions of art. 19 and 55 of the Russian Con-stitution is very debatable issue. Although Constitutional Court of the Russian Federation in its decisions confirms the constitutional empowerment of the constituent entities with the authority to establish in its laws the administrative responsibility for violation regional and municipal rules, such decisions are controversial. It may be useful to consolidate adminis-trative and tort law in the exclusive jurisdiction of the Russian Federation.Conclusion. The provisions of Federal legislation that let constituent entities of the Russian Federation to establish administrative responsibility for administrative offenses are not fully comply with the constitutional provisions, despite the opinion of the Constitutional Court of the Russian Federation.